Developing the hybrid model (waqf & zakat) for improving the zakat recipients’ healthcare In Selangor - Shaiq Ahmad, Ghafoorzai; Bilal Khan, Mohammad; Patel, Ibadurrehman; Shehbaz, Damkar Mohammed; Sharofiddin, Ashurov (IIUM Press, 2021)
The paper aims to develop a system that will strengthen zakat recipients' healthcare through coordination between waqf and zakat institutions. According to sources, Selangor has a lot of waqf and zakatreserves that are not being used. To resolve these issues and optimize the usage of barren and underused properties of Waqf and Zakat, a better management structure is needed. To accomplish the objective, this research employs a qualitative approach. It is found in the study that the Zakat and Waqf can be used for investment purposes; however, return from these investments should be used for the intended purpose and,i.e., to ensure social well-being, especially of the marginalized groups of society. The proposed model holds significance in improving the healthcare of zakat recipients and leading the society towards achieving social well-being and better living standards. This study's results may enhance the policymakers' understanding and contribute to better utilization of Zakat and Waqf assets. Besides, it will also enhance zakat collection and distribution and contribute toWaqf and Zakat funds' efficient management. There are certain limitations to the study in data availability, such as official data for waqf land in Selangor is available till December 31, 2016.